(untitled) (The Pakistan Development Review, 2018)
The book entitled, Heat Greed and Human Need: Climate Change, Capitalism and Sustainable Wellbeing provides-an economic, social, and political analyses of the drivers of climate change. It investigates the political economy of capitalism and offers a long-term, interdisciplinary analysis to mitigate the effect of climate change on temperature, while also improving equity and social justice. The book is divided into two parts. Part 1 covers the conceptual and global issues while Part II focuses on the affluent world. The climate change is a global threat, posing existential dangers while at the same time posing wicked dilemmas in coordinating global action to constrain it. These issues are of epochal significance and provide sufficient justification for Part I. The second part analyses `welfare states’ of the developed world. It addresses how far they are dependent on the carbon economy and how they can be reformed to pursue both carbon mitigation and human welfare simultaneously. This leads into analyses of policy-making under different scenarios of production, consumption and growth. Different `eco-social’ policies that could combine sustainable livelihood with human well-being are proposed and conclbsibm4 are summarised.